Psychosocial experiences of young adults diagnosed with acute leukemia during hospitalization for treatment - Albrecht, Tara A. (J Hosp Palliat Nurs, 2019)
The diagnosis of cancer for anyone is a time of fear and uncertainty. For young adults (YA) diagnosed with acute leukemia (AL) there are the additional challenges related to lengthy aggressive in-hospital treatment, multiple concurrent symptoms and decreased wellbeing. The purpose of this study was to explore the experiences of YAs with AL undergoing induction chemotherapy. This study used a nested qualitative longitudinal design with a convenience sample. Qualitative data was collected using semi-structured interviews and participants were invited to maintain journals. The semi-structured interviews were audiotaped, transcribed and loaded into Atlas.ti for analysis. Common themes and categories were verified and used to disseminate the findings. Seven YA, mean age 32 (+/− 4) years participated in this study. Three thematic classifications emerged: Getting Through, Supported yet Isolated, Information Exchange Preferences, that detail how these YA processed and coped during treatment. The findings from this study provide important insights for nurses regarding coping mechanisms that YA apply, which included relying on technology and social media platforms. Additionally, the YAs in this study discussed their need for information. The findings from this study may provide insights for clinicians currently caring for YA with AL, while also directing future palliative care research endeavors.